Glycemic and satiety response to three mexican honey varieties - Palomo de León, Brenda A.; Castro, Heriberto; Sánchez Murillo, Mayra E.; de la Garza, Ana Laura; Rodríguez Romero, Beatriz Adriana; Alonzo Macías, Maritza; Ramírez Jiménez, Aurea K.; Cardador Martínez, Anaberta; Hernández Salazar, Marcelo (Multidisciplinary Digital Publishing Institute, 2023)
Honey is considered one of the last untreated natural food substances, with a complex composition. It is produced by bees (Apis mellifera) from nectar. The glycemic index (GI) is a physiological assessment of a food’s carbohydrate content via its effect on postprandial blood glucose concentrations. This study evaluated the GI and the satiety response to three Mexican types of honey administered to 26 healthy volunteers. The fructose values ranged from 272.40 g/kg to 395.10 g/kg, while the glucose value ranged from 232.20 g/kg to 355.50 g/kg. The fructose/glucose (F/G) ratio of honey was 1.45, 1.00, and 1.17 for highland, multifloral, and avocado honey, respectively. Highland and avocado honey were classified as medium-GI (69.20 ± 4.07 and 66.36 ± 5.74, respectively), while multifloral honey was classified as high-GI (74.24 ± 5.98). Highland honey presented a higher satiety values response than glucose. The difference in GI values and the satiety response effect of highland honey could be explained by its different carbohydrate composition and the possible presence of other honey components such as phytochemicals. Honey, especially avocado, could therefore be used as a sweetener without altering significantly the blood glucose concentration.